Switching Dynamics and Energy Storage Properties of Fluorite‐Structured Materials. Issue 1 (8th December 2022) - Ali, Faizan; Ali, Tarek; Abbas, Akmal; Lehninger, David; Iqbal, Muhammad Faisal; Fadhali, Mohammed M.; Shaaban, Ibrahim A.; Czernohorsky, Malte; Seidel, Konrad; Kämpfe, Thomas
Abstract : The fluorite‐structural ferroelectric (FE) and antiferroelectric (AFE) materials exhibit promising applications in memories and energy storage devices. However, understanding frequency‐dependent polarization and phase switching, which is very important for electronic device performance, is still a critical problem. Herein, frequency‐dependent polarization and phase switching of the Si‐doped HfO2 ‐based metal–dielectric–metal capacitors with FE and AFE‐like thin films, respectively, are investigated. The Kolmogorov–Avrami–Ishibashi (KAI) and nucleation‐limited switching models are used to attain detailed information on polarization switching of Si‐doped HfO2 FE thin films. Moreover, energy storage properties of Si‐doped HfO2 AFE thin films are investigated at a wide measurement frequency range (50 Hz–100 kHz). Both energy storage density and energy storage efficiency decrease with increasing frequency. However, energy loss increases with increasing testing frequency. Abstract : Herein, the frequency‐dependent switching and energy storage properties of Si‐doped HfO2 thin films are investigated. The coercive field of Si:HfO2 ferroelectric thin films increases with increasing measurement frequency. The switching fields for the tetragonal‐ (t‐) to orthorhombic‐ ( o ‐) phase and o ‐ to t ‐phase of Si:HfO2 antiferroelectric‐like thin films increase and decrease, respectively, with increasing testing frequency.